The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1034/j.1600-051x.2000.027004217.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for drug‐induced gingival overgrowth

Abstract: The identification of risk factors associated with both the prevalence and severity of drug-induced gingival overgrowth is important for all parties involved with this unwanted effect. Both periodontologist and patient have an important rôle to play in improving oral hygiene and gingival health. Likewise, there is always an opportunity to establish a close liaison between the patient's physician and the periodontologist to try and identify alternative drug regimens that can help reduce the impact of this unwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
284
2
18

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(314 citation statements)
references
References 51 publications
10
284
2
18
Order By: Relevance
“…1 These medications include the immune suppressor cyclosporine-A (CsA), the anti-seizure drug phenytoin (PNT), and calcium channel blockers (CCBs). 2,3 The incidence of this side effect can be as high as 70% in transplant patients, 65% in epileptics, and 30% in hypertensive patients. 4,5 In 1997, Iacopino et al 6 reported that the clinical presentation of inflamed and hyperplastic gingival tissues are associated with specific macrophage phenotypes which express the essential platelet derived growth factor-beta (PDGF-B) in PNT-induced hyperplastic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…1 These medications include the immune suppressor cyclosporine-A (CsA), the anti-seizure drug phenytoin (PNT), and calcium channel blockers (CCBs). 2,3 The incidence of this side effect can be as high as 70% in transplant patients, 65% in epileptics, and 30% in hypertensive patients. 4,5 In 1997, Iacopino et al 6 reported that the clinical presentation of inflamed and hyperplastic gingival tissues are associated with specific macrophage phenotypes which express the essential platelet derived growth factor-beta (PDGF-B) in PNT-induced hyperplastic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…8 At the same time, it has been suggested that drug-induced gingival overgrowth is related to factors such as treatment duration, presence of bacterial biofi lm and gingival infl ammation. 9,10 Therefore, our hypothesis was to explore in rats treated with diltiazem whether gingival infl ammation, secondary to a sucrose-rich diet, would induce gingival alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the pathogenesis of drug-induced gingival enlargement is uncertain and confl icting and has been related to several factors, namely age, gender, treatment duration, plasmatic and salivary drug concentration, presence of bacterial biofi lm, gingival tissue infl ammation, genetics and synergism with other medicaments. 9,10 Considering that these factors are important determinants of gingival overgrowth, the purpose of this study was to evaluate the infl uence of diltiazem, in different doses and periods, in combination with a sucrose-rich diet on gingival alterations in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien es aceptada su relación directa con fármacos y el factor genético, entre otros, el rol del biofilm bacteriano (placa dental) ha sido controvertido [5][6][7][8][9] .…”
Section: Gingival Enlargement Can Be An Adverse Effect Of Ciclosporinunclassified
“…Algunos autores recomiendan cambiar el término hiperplasia por el de agrandamiento gingival, ya que el incremento en el tamaño del tejido es debido a un aumento en su estroma y no al número de sus células constituyentes 1 , término que ocuparemos para este trabajo. Se define como agrandamiento gingival al aumento exagerado y desfigurante del volumen de la encía, asociándose su aparición principalmente a fármacos 2,3 .Se describe que 30% de los pacientes que toman ciclosporina A desarrollan agrandamiento gingival, con una alta tasa de recidiva, aumentando su prevalencia al doble al encontrarse junto a nifedipino 4 , no poseyendo una etiología única, sino una serie de factores asociados 5,6 . Si bien es aceptada su relación directa con fármacos y el factor genético, entre otros, el rol del biofilm bacteriano (placa dental) ha sido controvertido [5][6][7][8][9] .…”
unclassified